Analisis Manajemen Rantai Pasok pada Peternakan Ayam Petelur Ras - Wotavia, Celinda Yunilatul; Murnawan, Hery (Fakultas Teknik UMRI, 2025)
Blitar Regency is a major center for layer egg production in Indonesia, with one of its key producers being Artomoro Farm, located in Ngaringan Village, Gandusari District. This study analyzes the supply chain management and financial performance of Artomoro Farm over a 25-month production cycle. The upstream subsystem includes the supply of DOCs, feed, vitamins, vaccines, and medicines from various national suppliers. The farm houses 80,000 laying hens in a combination of close house and open house systems, achieving over 95% egg productivity and a monthly mortality rate of 0.5%. The feed warehouse has a capacity of 2,000 sacks (50 kg each). The downstream subsystem involves egg distribution to Jakarta, Surabaya, and Blitar, along with the sale of spent hens and chicken manure. With an initial investment of IDR 6.2 billion, the farm reached its break-even point in the 14th month and generated a final profit of IDR 13.4 billion. Results indicate an efficient, integrated, and sustainable supply chain.